2020
DOI: 10.1002/cam4.2926
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral maintenance chemotherapy and predictive value of circulating EBV DNA in metastatic nasopharyngeal carcinoma

Abstract: Background/Objectives: Oral maintenance chemotherapy can effectively prolong overall survival (OS) in many types of metastatic cancer, but its role in metastatic nasopharyngeal carcinoma (mNPC) is unclear. In this study, the efficacy of oral maintenance chemotherapy in mNPC and the effectiveness of circulating tumor EBV-DNA for screening patients were evaluated. Methods: Between June 2016 and December 2017, 141 patients with mNPC who received platinum-based systemic chemotherapy were included (median follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
3
9
0
Order By: Relevance
“…Well-designed prospective clinical trials are expected to explore how to optimize the treatment strategy of PMD patients. Previous studies have also confirmed that the undetectable EBV DNA levels after 4–6 weeks of chemotherapy were a good prognostic factor and a biomarker to filter out beneficiaries of maintenance chemotherapy in metastatic NPC [34] . Unfortunately, there is no standard protocol for EBV DNA detection; only a few centers have a sensitivity and specificity of >90% for EBV DNA detection [35] , [36] , [37] .…”
Section: Discussionmentioning
confidence: 74%
“…Well-designed prospective clinical trials are expected to explore how to optimize the treatment strategy of PMD patients. Previous studies have also confirmed that the undetectable EBV DNA levels after 4–6 weeks of chemotherapy were a good prognostic factor and a biomarker to filter out beneficiaries of maintenance chemotherapy in metastatic NPC [34] . Unfortunately, there is no standard protocol for EBV DNA detection; only a few centers have a sensitivity and specificity of >90% for EBV DNA detection [35] , [36] , [37] .…”
Section: Discussionmentioning
confidence: 74%
“…Another study showed that EBV DNA and some PET parameters were unfavourable prognostic factors [104]. However, one study showed that post-treatment EBV DNA titres after 1st-line platinumbased chemotherapy was not prognostic of OS [105].…”
Section: Value Of Plasma Ebv Dna In Recurrent or Metastatic Npcmentioning
confidence: 99%
“…This cfDNA is released from NPC cells during apoptosis and can be extracted from serum and then detected by RT‐qPCR targeting the EBV BamHI‐W region 130 . In addition to screening EBV‐positive people in the population and taking preventive measures in time, this connection can also be used to monitor cancer progression and therefore evaluate the efficacy of chemotherapy of immunotherapy 131,132 or adjust treatment in time 133 . It has also been reported that shallow‐depth sequencing of cfDNA could be a promising standardized approach 134 …”
Section: Cfdnas Derived From Human Tumor Virusesmentioning
confidence: 99%